ANALISIS KONTRIBUSI PAJAK DAERAH DALAM MENINGKATKAN PENDAPATAN ASLI DAERAH KOTA SAMARINDA TAHUN 2014-2018 - Devi Vitria (ADMINISTRASI PUBLIK, 2021)
Analysis of Regional Tax Contribution in IncreasingLocal Revenu of Samarinda City in 2014-2018 The purpose of this study is to determine the contribution of local taxes in helping to increase local revenue Samarinda City in 2014-2018. This study uses qualitative methods, for data collection techniques carried out by documentation and interview. And the data analysis technique used is the analysis of contributions and effectiveness to find out how much the contribution and effectiveness of each type of local tax in 2014-2018, From the results of data analysis it can be concluded that: the largest contributors first are road lighting taxes with an average contribution of 20.00%, secondly the tax on the acquisition of land and building rights 12.13%, the third the land and rural building tax and urban 8.70%, the fourth restaurant tax 9.05%, the fifth hotel tax 5.32%. And the lowest contributing is the ground water tax with an average contribution of 1.18% and swallow bird nest tax of 0.32%. The level of effectiveness of each type of regional tax in Samarinda city falls into the effective category.